Dilemma between phonetic function and respiratory function about phonosurgery in the laryngeal trauma and inevitable dilemma - SHIN, Takemoto; WATANABE, Hiroshi; TSUDA, Kuniyoshi; FUKUYAMA, Tuyako; KAWASOE, Michiru; MORIKAWA, Ikuro; FUKAURA, Junichi (OTOLOGIA FUKUOKA, 1993)
A grade, extent or complexity of laryngeal traumas is variable. Therefore, how to cure by phonosurger-y seems to one of key factors about complete functional curability. However, all injured cases would be analyzed in two type of injury. One of injury involving the laryngeal framework and other of injury involving the intralaryngeal cavity. These findings lead us to a destination of treatment of individual and variable independent applied way of phonosurgery. In this study, beforementioned typical two subjects with laryngeal injury were cured via individual most profitable approach of both an extraframework reposition and an intralaryngeal repair. These results were successful from phoniatric aspects.